2018
DOI: 10.1007/s00894-017-3575-6
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical descriptions of novel triplet germylenes M1-Ge-M2-M3 (M1 = H, Li, Na, K; M2 = Be, Mg, Ca; M3 = H, F, Cl, Br)

Abstract: In a quest to identify new ground-state triplet germylenes, the stabilities (singlet-triplet energy differences, ΔE) of 96 singlet (s) and triplet (t) M-Ge-M-M species were compared and contrasted at the B3LYP/6-311++G**, QCISD(T)/6-311++G**, and CCSD(T)/6-311++G** levels of theory (M = H, Li, Na, K; M = Be, Mg, Ca; M = H, F, Cl, Br). Interestingly, F-substituent triplet germylenes (M = F) appear to be more stable and linear than the corresponding Cl- or Br-substituent triplet germylenes (M = Cl or Br). Triple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…[19] In order to characterize the stationary points as minima and to evaluate zero-point vibrational energy, harmonic vibrational frequencies are computed for restricted singlet and (unrestricted triplet) germylenes at (U)B3LYP/6-311++G**. [18,19] The nucleophilicity index (N) is calculated as N = E HOMO (Nu) − E HOMO (TCNE) , where tetracyanoethylene (TCNE) is chosen as the reference. [36,37] The global electrophilicity (ω) [38] is computed as ω = (μ 2 /2η), where μ is the chemical potential (μ ≈ (E HOMO + E LUMO )/2) and η is the chemical hardness (η = E LUMO − E HOMO ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[19] In order to characterize the stationary points as minima and to evaluate zero-point vibrational energy, harmonic vibrational frequencies are computed for restricted singlet and (unrestricted triplet) germylenes at (U)B3LYP/6-311++G**. [18,19] The nucleophilicity index (N) is calculated as N = E HOMO (Nu) − E HOMO (TCNE) , where tetracyanoethylene (TCNE) is chosen as the reference. [36,37] The global electrophilicity (ω) [38] is computed as ω = (μ 2 /2η), where μ is the chemical potential (μ ≈ (E HOMO + E LUMO )/2) and η is the chemical hardness (η = E LUMO − E HOMO ).…”
Section: Methodsmentioning
confidence: 99%
“…[10][11][12][13][14][15][16][17] Also, they are applied as precursors in the lowtemperature synthesis of Ge-rich semiconductors via chemical vapor deposition during the production of components of nanomaterials. [18] In contrast to carbenes, germylenes have mainly singlet ground states. [19][20][21] In fact, the lone pair electrons on -G̈e-increase s atomic orbital character with increasing atomic size.…”
Section: Introductionmentioning
confidence: 99%
“…[3] Also, NHGes are applied as precursors in the low-temperature synthesis of Ge-rich semiconductors via chemical vapor deposition during the production of components of nanomaterials. [4] In 1987, Veith succeeded to synthesize the first NHGe (I) with a four-membered structure stabilized by two nearby nitrogen atoms (Scheme 1). [5] In contrast to normal carbenes, NHGes have mainly singlet ground states.…”
Section: Introductionmentioning
confidence: 99%
“…In 1991, Arduengo and coworkers synthesized colorless crystals of 1,3‐di‐l‐adamantylimidazol‐2‐ylidene, which was the first stable NHC. After several years, theoretical researchers found that triplet N‐heterocyclic silylenes and germylenes could also be stable . In fact, due to the importance of triplet ground‐state silylenes and germylenes in chemical semiconductor manufacturing, vapor deposition and the aerospace and photonics industries, the preparation, and theoretical calculation of these isomers have become one of the most important topics in modern organosilicon and germanium chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, due to the importance of triplet ground‐state silylenes and germylenes in chemical semiconductor manufacturing, vapor deposition and the aerospace and photonics industries, the preparation, and theoretical calculation of these isomers have become one of the most important topics in modern organosilicon and germanium chemistry. Recently, some studies indicated that the EPR spectrum and X‐ray crystallography provide unambiguous evidence for silylene and germylene triplet ground state . In 2011, Momeni et al researched at triplet NH‐vinylidene silylenes with (NRCH 2 ‐CH 2 NR)Si═Si and (NRCHCHNR)Si═Si structures …”
Section: Introductionmentioning
confidence: 99%